Caring, control and compliance: nursing's struggle to be audible - Middleton, C.B. (2013)
There are many situations in healthcare delivery in the UK where nurses are the dominant workforce or have expert practitioners working directly with clients, yet rarely, apparently, are they involved in national healthcare policy development nor do they have significant input into how they are expected to practise.